Terapi Bermain Puzzle Untuk Meningkatkan Kemampuan Kognitif Pada Anak Tunagrahita Ringan - Rafael Lisinus Ginting; Jessica Cintya; Nadia Fadillah; Nazwa Salsabila Marpaung; Shafiqa Nayla Azzahra; Tari Ramadhani; Elovani Martahelena Lubis; Giovanni Paulina Pakpahan; Nila Arfiena; Anandini Naomi Putri Siregar (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Acute Coronary Syndrome (ACS) is a major cardiovascular problem because it causes high rates of hospitalization and mortality. The clinical manifestations of ACS are that the patient feels pain and discomfort that is not specific in the chest and legs radiating to the neck, left shoulder and arms and back then accompanied by cold sweat, nausea, vomiting, weakness and dizziness and can faint which occurs suddenly with high intensity. Objective: To find out the results of applying Thermotherapy therapy to relieve chest pain in patients with Acute Coronary Syndrome. Moewardi Surakarta. Method: This type of research is a descriptive case study. The application was carried out on 2 patients selected by purposive sampling method with inclusion and exclusion criteria. Thermotherapy is carried out for 10-20 minutes 1x/day for 3 days. The research instrument used SOP foot massage, hemodynamic status observation sheets, and informed consent. Results: After being given the application to both respondents for 1 time a day for 3 consecutive days, a decrease in the level of the chest pain scale was found in the patient Mr. S with a pain scale level before being carried out by Thermotherapy therapy, severe pain and after being carried out by Thermotherapy therapy for 1 time in 3 consecutive days to mild pain. Meanwhile, in the patient Mr. A with the level of pain scale before the Thermotherapy therapy is severe pain and after the Thermotherapy therapy is done for 1 time in 3 consecutive days it becomes mild pain. Conclusion: there is a reduction in the chest pain scale in patients with Acute Coronary Syndrome at RSUD Dr. Moewardi Surakarta after being given thermotherapy.